Long-term effect of SARS-CoV-2 infection: Post-Covid-19 neurological syndrome - Caballero-Alvarado, José (2022)
Background: The COVID-19 pandemic has caused approximately 182 million cases and nearly four million deaths worldwide, most frequently involving people between 25 and 64 years of age. This infection primarily affects the respiratory system, but other organs and systems can be affected in the short term, such as the neurological system. A large population of patients has managed to overcome the SARS-CoV-2 infection, however, a serie of late clinical manifestations have begun to be reported, basically neuropsychiatric, including anxiety, depression, disorder of sleep, muscle pain, dizziness, headaches, fatigue, anosmia, among others; this set of late manifestations has been called post-Covid-19 neurological syndrome and requires, on the one hand, the attention of the medical community to investigate the late manifestations or sequel of this disease and, on the other hand, medical vigilance when consulting patients with these manifestations.